2016
DOI: 10.1097/01.asw.0000481115.78879.63
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Pressure Ulcers Including Suspected Deep Tissue Injury in Nursing Home Facility Residents

Abstract: The MDS data support Defloor's model and inform clinicians, educators, researchers, and policymakers on risk factors associated with PrUs and sDTI in NH residents in the United States participating in Medicare and Medicaid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 32 publications
3
44
0
4
Order By: Relevance
“…However, the proportions of these high‐risk groups in acute hospital care appear to be lower compared to aged and long‐term care settings. Evidence indicates that the majority of long‐term care receivers is at a high PU risk due to a number of functional impairments . Thus, the much lower numbers of QIs for this setting is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proportions of these high‐risk groups in acute hospital care appear to be lower compared to aged and long‐term care settings. Evidence indicates that the majority of long‐term care receivers is at a high PU risk due to a number of functional impairments . Thus, the much lower numbers of QIs for this setting is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Timely healing is also important for reducing health care costs, which, for pressure ulcer treatment, can be substantial (Gallagher, 2011). Pressure ulcers among older individuals in long-term care facilities are a global problem with prevalence ranging from 10% to 30% (Ahn, Cowan, Garvan, Lyon, & Stechmiller, 2016; Bours, Halfens, Abu-Saad, & Gro, 2002; Capon, Pavoni, Mastromattei, & Di Lallo, 2007; Gunningberg, Hommel, Baath, & Idvall, 2013; Lahmann, Halfens, & Dassen, 2005; Levinson, 2014; Tannen, Bours, Halfens, & Dassen, 2006). The overall prevalence of Stage 2 to 4 pressure ulcers at NH admission in the United States (U.S.) ranges between 5%-20% (Baumgarten et al, 2004; Harms et al, 2014), but among minority NH admissions in the U.S., the prevalence is nearly twice that of Whites (Baumgarten et al, 2004; Harms et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Howard and Taylor's () study which analysed Minimum Data Sets (MDSs) in the Atlanta Region from 1999–2002, stage 2 PIs which are visual breaks in the skin (NPUAP, ) were the most common stage on admission, occurring at a rate of 2.6% in the overall study sample. A consistent trend found across a number of the studies reviewed showed that people with DSTs had the highest risk of higher stages of PI (Ahn, Cowan, Garvan, Lyon, & Stechmiller, ; Baumgarten et al., ; Cai et al., ; Fogerty, Guy, Barbul, Nanney, & Abumrad, ; Gerardo et al. ; Harms et al., ; Li, Yin, Cai, Temkin‐Greener, & Mukamel, ; VanGilder, MacFarlane, & Meyer, ).…”
Section: Resultsmentioning
confidence: 67%
“…The literature revealed significant variation in the terminology used for the description of skin tones (Salcido, ), and there was exclusion and lack of appropriate ethnic minority sample sizes to draw solid conclusions about identification of PIs. In some US‐based studies (Ahn et al., ; Gerardo et al., ; Harms et al., ), figures were collated about people categorised as Hispanics; nonetheless, these do not relate to the population structure of countries such as the United Kingdom, Australia or Europe, meaning that generalisability outside of the USA is restricted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation